Doc Martin. Series 2 [videorecording (DVD)] - Bolt, Ben, 1952-; Clunes, Martin, 1961-; Catz, Caroline; Cole, Stephanie, 1941-; McNeice, Ian (Distributed by Acorn Media, 2009)
As a hard-charging London surgeon, Martin Ellingham didn't need a bedside manner. His patients were unconscious, so he could be as rude and arrogant as he pleased. All that changes when he develops a crippling fear of blood and is forced to give up surgery. Now a GP in a sleepy, picturesque Cornish fishing village, Doc Martin offends everyone in town, including the one person he wants to impress, beautiful teacher Louisa Glasson. Getting her attention proves even more difficult when Louisa's old flame returns to the village and becomes his new rival.